Pregnant Women’s Mental Health Status and its Related Factors Amidst COVID-19: A Cross- Sectional Study - Thapa, Pratima; Dhakal, Binita; Shrestha, Upasana; Adhikari, Srijana Gautam; Shrestha, Sunayana (Journal of Lumbini Medical College, 2021)
Introduction: Since the emergence of COVID-19 pandemic, it has challenged the psychological aspect of everyone. Pregnant women being the vulnerable group are most likely to be at increased risk. This study aimed to assess the mental health status of the pregnant women residing in Nepal during COVID-19. Methods: A cross-sectional online study was carried out among 368 pregnant women during lockdown using Perceived stress scale-10, Generalized Anxiety Disorder-7 scale and Edinburg Perinatal Depression Scale. Data were analyzed using descriptive and inferential statistics. Results: The mean age of the participants was 27.06±4.64years. Getting infected with the virus (71.7%) was the major fear and inadequate antenatal checkup (61.1%) was the major effect experienced by the participants. The prevalence of stress, anxiety and depression was 41%, 28.5% and 33.2% respectively. Age, salary status of oneself and their husband, healthcare frontliner in the family and effect of social distancing were significantly associated with perceived stress. Age, education, employment, monthly income, trimester and effect of social distancing were significantly associated with anxiety. Salary status of husband, trimester, parity, being infected with COVID-19 and effect of social distancing were associated with depression. Conclusion: High prevalence of mental health disorders during COVID-19 outbreak suggests the importance of special attention on monitoring the maternal mental health status during such public health emergencies. Measures such as awareness program targeted to pregnant women and health education programs on how to cope during the pandemic situations should be made effective to rule down the mental health burden of COVID-19.